163 Morbidity of Presumed Temporary Loop De-Functioning Stomas in Patients with Colorectal Cancer. (12th October 2021) - Alfred, J; Macdonald, S; Kalaiselvan, R
Abstract: Objectives: The incidence of parastomal hernia (PSH) can be up to 80% of patients who have a stoma following abdominal surgery (1). Surgical intervention is required in 70% of patients due to pain, obstructive symptoms, or stoma appliance issues (2). This study aims to show the morbidity related to a presumed temporary loop stoma. Method: This was a retrospective cohort study of all left-sided colorectal cancer resections undertaken in a single centre. Electronic healthcare records and Picture Archiving and Communication System (PACS) were used to gather data on patient demographics, operative details and details of de-functioning stoma fashioned. Morbidity related to de-functioning stoma was determined based on hospital admissions and length of inpatient stay related to stoma, complications in relation to the stoma, return to theatre, stoma reversal and fate of stoma site. Results: 147 patients (87 M; 60 F, median age 69 (23-93)) underwent left sided colorectal cancer resections at a single centre. In total, 50 de-functioning loop stomas were fashioned (49 loop ileostomies and 1 loop colostomy.) At a median follow-up of 23 months (8-44), prior to reversal, 12 PSH were identified. 38 of the de-functioning stomas were reversed at a median time of 11 months (1-44), 5 of which were emergency procedures due to obstruction (n = 3) or high output (n = 2). There were 9 stoma related re-admissions identified in 7 patients. Conclusions: Presumed temporary defunctioning loop ileostomies in Low anterior resections is associated with significant morbidity, but low risk in terms of life-threatening complication.